Interleukin-22-induced Î²â€‘defensin-2 expression by intranasal immunization with Streptococcus pneumoniae RrgB epitopes - Mufida, Diana Chusna; Saputra, Antonius Dwi; Hermansyah, Bagus; Agustina, Dini; Shodikin, Muhammad Ali; Armiyanti, Yunita (Faculty of Medicine, Universitas Trisakti, 2022)
BackgroundStreptococcus pneumoniae causes pneumococcal disease, which is responsible for millions of deaths worldwide. Various pneumococcal vaccine candidates have been developed to prevent S. pneumoniae infection, one of which is an epitope-based vaccine. This study aimed to prove that intranasal immunization with each of the five S. pneumoniae RrgB epitopes can induce a mucosal immune response by increasing the Î²-defensin-2 concentration through upregulation of interleukin (IL)-22 expression. MethodsAn experimental laboratory study was conducted using 28 male Wistar rats aged 3-4 months, that were randomly divided into 7 groups containing four rats each. Group 1 was given 40 mL of phosphate-buffered saline (PBS) only (control group). Group 2 was the adjuvant group that received 40 mL PBS containing 2 Ã¬g cholera toxin B (CTB), and groups 3-7 were immunized with 40 mL PBS containing a combination of adjuvant and one of the five different S. pneumoniae RrgB epitopes. The concentrations of IL-22 and Î²-defensin-2 from nasal rinse examination were measured by means of ELISA. The Kruskal-Wallis test, followed by the Mann-Whitney post-hoc test were used for statistical analysis. ResultsRats immunized with the adjuvant-epitope combination had significantly higher Î²-defensin-2 and IL-22 levels than the control group (p=0.030; p=0.018, respectively), according to the Kruskal-Wallis test. And the Mann-Whitney statistical test, showed there was a significant increase in Î²-defensin-2 and IL-22 levels. ConclusionsIntranasal immunization with epitope 1 of the S. pneumoniae RrgB can increase Î²-defensin-2 expression significantly and has a greater potential to be developed into a pneumococcal vaccine.